PENATALAKSANAAN MANAJEMEN PERAWATAN LUKA PADA PASIEN DENGAN VULNUS.LASERATUM REGIO MENTALIS DI RUANGAN IGD RS TK II PELAMONIA MAKASSAR - Jeni Riana Bulu; Tutik Agustini; Andi Yuliana; Yusrah Aqiyah (Jurnal Kesehatan, 2026)
Vulnus Laceratum, Or Lacerated Wound, Is A Type Of Open Wound Characterized By The Tearing Of The Skin And Underlying Tissue Due To Trauma. This Type Of Wound Typically Has An Irregular Shape With Jagged Edges, Often Caused By Pulling Or Scraping From Blunt Objects Such As The Edge Of A Table Or Parts Of A Motor Vehicle. One Technique That Can Be Applied To Reduce The Risk Of Infection Is Wound Care Using Transparent Film Dressing. Research Results: This Study Used A Descriptive Method With A Case Study Approach. The Research Subjects Were Two Individuals Who Experienced Vulnus Laceratum. Infection Risk Was Measured Using An Infection Risk Checklist. In Subject I, There Was A Decrease In Infection Risk Marked By Improvement In Redness, Swelling, And Pain. In Subject II, Redness, Swelling, And Pain Also Improved. The Application Of Transparent Film Dressing For Three Days Proved To Be A Potential Alternative Intervention To Reduce The Risk Of Infection. Conclusion: The Results Of This Case Study Showed A Decrease In Infection Risk In Both Subjects, Indicated By Improvements In Redness, Swelling, And Pain